2020
DOI: 10.13168/agg.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of GRACE and GLDAS derived hydrological loading and the impacts on the GPS time series in Europe

Abstract: The surface displacement caused by hydrological loading makes an important contribution to the non-linear crustal movement observed at the International Global Navigation Satellite System Service (IGS) stations. In this paper, the amplitude, correlation, and root mean square (RMS) of the vertical displacement time series signals of 47 IGS stations are used to analyze which data of Gravity Recovery and Climate Experiment (GRACE) or Global Land Data Assimilation System (GLDAS) can better reflect the hydrological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The KBRR inversion using SF for both cases of the Congo and Nile basins, yield results that are very comparable with those of the GLDAS model for frequency (temporal variations) and latitudinal zonation (spatial variations). In terms of intensity, a relatively constant and clear bias is observed like many authors have observed before (in South America [37], Africa [38], Poland [39], and at global scale [40]) and it corresponds, in our case, to a factor~2. So, in order to be able to compare the estimated SF maps, we have chosen to divide the outputs of the GLDAS simulation by 2, at least to ease the graphical representation using the same color scale (Figure 3).…”
Section: Analysis Of the Slepian Coefficient Truncationsupporting
confidence: 88%
“…The KBRR inversion using SF for both cases of the Congo and Nile basins, yield results that are very comparable with those of the GLDAS model for frequency (temporal variations) and latitudinal zonation (spatial variations). In terms of intensity, a relatively constant and clear bias is observed like many authors have observed before (in South America [37], Africa [38], Poland [39], and at global scale [40]) and it corresponds, in our case, to a factor~2. So, in order to be able to compare the estimated SF maps, we have chosen to divide the outputs of the GLDAS simulation by 2, at least to ease the graphical representation using the same color scale (Figure 3).…”
Section: Analysis Of the Slepian Coefficient Truncationsupporting
confidence: 88%
“…The comparison to the state of the art in literature is not directly possible, as every study uses a different set of stations and loading models. Similar studies, which also focus on the area of Europe, are Bian [5], achieving an average RMS reduction of 16-25%, and Springer et al [28], obtaining 20-30% with NTAL and NTOL and adding another 7% with HYDL.…”
Section: Reduction Of Gnss Residuals By Environmental Loadingsmentioning
confidence: 66%
“…In the southern hemisphere, most of their test stations were located closer to coastal regions, and the assumption was that the missing improvement can be traced back to mis-modeled tropospheric zenith delay. Recent studies look into the comparison of different environmental surface loading models [5][6][7][8], the comparison of geophysical models and information drawn from the Gravity Recovery and Climate Experiment (GRACE) [9], and the assimilation of both approaches [10,11]. Up to today, there is no standardized procedure of modeling and reducing the station position by environmental surface loadings [12].…”
Section: Introductionmentioning
confidence: 99%
“…Non-tidal oceanic loading appears to be significant only for the coastal regions and islands, while nontidal atmospheric loading seems to dominate over Eastern Europe and Asia (Brondeel and Willems 2003;Williams and Penna 2011). Williams and Penna (2011) and Bian et al (2020) showed that removing loading-predicted displacements from the Global Positioning System (GPS) displacement time series leads to an improvement in their standard deviations. The standard deviations improve even more when the same loading effects are applied at the observation level (Dach et al 2011;Männel et al 2019).…”
Section: Introductionmentioning
confidence: 99%